The Association of Obesity and Cardiometabolic Traits with Incident HFpEF and HFrEF - Savji, Nazir (JACC Heart Fail, 2018)
OBJECTIVES: We evaluated the associations of obesity and cardiometabolic traits with incident heart failure with preserved vs reduced ejection fraction (HFpEF vs HFrEF). Given known sex differences in HF subtype, we examined men and women separately. BACKGROUND: Recent studies suggest that obesity confers greater risk of HFpEF vs HFrEF. Contributions of associated metabolic traits to HFpEF are less clear. METHODS: We studied 22,681 participants from 4 community-based cohorts followed for incident HFpEF vs HFrEF (EF> vs ≤50%). We evaluated the association of body mass index (BMI) and cardiometabolic traits with incident HF subtype using Cox models. RESULTS: The mean age was 60±13 years, 53% were women. Over a median follow-up of 12 years, 628 developed incident HFpEF and 835 HFrEF. Greater BMI portended higher risk of HFpEF compared with HFrEF (HFpEF: HR 1.34 per 1 standard deviation (SD) increase in BMI; 95% CI 1.24-1.45 vs HFrEF: HR 1.18; 95% CI 1.10-1.27). Similarly, insulin resistance (HOMA- IR) was associated with HFpEF (HR 1.20 per 1 SD, 95% CI 1.05-1.37), but not HFrEF (HR 0.99, 95% CI 0.88–1.11; P<0.05 for difference HFpEF vs HFrEF). We found that the differential association of BMI with HFpEF vs HFrEF was more pronounced among women (P for difference HFpEF vs HFrEF=0.01) when compared with men (P=0.34). CONCLUSIONS: Obesity and related cardiometabolic traits including insulin resistance are more strongly associated with risk of future HFpEF vs HFrEF. The differential risk of HFpEF with obesity appears particularly pronounced among women and may underlie sex differences in HF subtypes.